Peran Aplikasi Wargaku Dalam Mewujudkan Surabaya Smart City - Anak Agung Made Sri Santi Pratiwi (Universitas Sultan Ageng Tirtayasa, 2025)
The government endeavors to enhance the quality of life of citizens through the development of a Smart City, based on the principle of collaboration among government, society, and technology. In the implementation, public service must be integrated with ICT to support the dimension of a Smart City: Smart Governance. One city that successfully transforms into a Smart City in Indonesia is Surabaya with the excellent digital public service innovation: Wargaku application. The impact of the innovation raises questions about its role in achieving the Smart City concept, this research aims to analyze and explain the role of digital public service innovation that the Surabaya Government implemented through the Smart City dimension to achieve Surabaya Smart City (SSC). This study is qualitative research with a literature review approach, this study found that the various features of the Wargaku application have been accommodated by almost of the public service sector, and each available service in this application has been proven effective to supporting public services in Surabaya, an area of Smart Governance. Wargaku is a form of digital public service innovation that facilitates the top-bottom and bottom-top approach; therefore, this application is indirectly highly influential in the city and national governance.